2007
DOI: 10.1111/j.1467-8683.2007.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance in Bangladesh: Link between Ownership and Financial Performance

Abstract: This paper investigates empirically the effect of board ownership on firm performance in Bangladesh. By estimating single equation and simultaneous equation models on an unbalanced pooled sample of listed firms, it offers some new insight into the ownership-performance link in Bangladesh. Building on extant literature, it examines the ownership-performance relationship in an emerging market economy considering ownership as exogenous and as endogenous. The latter approach is favoured as recent empirical evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
124
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(148 citation statements)
references
References 49 publications
12
124
1
3
Order By: Relevance
“…As stated by Kapopoulos and Lazaretou (2007); firm size as calculated by the book value of total assets, had an inverse relation to performance. Firm size was negatively related to performance, as discovered by Farooque et al (2007). Firm size was positively and considerably linked with Tobin's q, as concluded by Hu and Izumida (2008).…”
Section: Firm Sizesupporting
confidence: 48%
“…As stated by Kapopoulos and Lazaretou (2007); firm size as calculated by the book value of total assets, had an inverse relation to performance. Firm size was negatively related to performance, as discovered by Farooque et al (2007). Firm size was positively and considerably linked with Tobin's q, as concluded by Hu and Izumida (2008).…”
Section: Firm Sizesupporting
confidence: 48%
“…A similar negative result was revealed between CEO tenure and firm performance by studies dedicated to the developing countries (e.g. Al Farooque et al, 2007;Bektas & Kaymak, 2009;Herly & Sisnuhadi, 2011;Jackling & Johl, 2009;Roselina, 2009;Tsai et al, 2006). On the other hand, other studies reported the absence of a relationship between CEO tenure and firm performance (e.g Bhagat & Bolton, 2008;Fidrmuc & Fidrmuc, 2007;Firth et al, 2006;Gibson, 2003;Kyereboah-Coleman, 2007).…”
Section: Ceo Tenure and Firm Performancementioning
confidence: 70%
“…Similarly, in the developing countries, Al Farooque et al (2007) found the relationship to be negative. Apart from that, there are some authors who found no relationship between CEO compensation and firm performance e.g, Adjaoud et al (2007).…”
Section: The Ceo Compensation and Firm Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Using a set of corporate governance indices based on 64 individual governance attributes, they found a strong and positive relation between firm-level corporate governance and firm valuation. Similar evidence is also found in emerging countries such as Venezuela (Garay & Gonzalez, 2008), India (Balasubramanian et al, 2010), China (Hu et al, 2010), and Bangladesh (Farooque et al, 2007). The review of extant literature on the relationship between the corporate governance and firm valuation shows that various factors relating to corporate ownership structure and internal governance mechanism, management and board structure, corporate leadership structure (CEO duality), and agency problem between different stakeholders could affect the valuation of corporate firms.…”
Section: Literature Review and Hypothesismentioning
confidence: 58%